2012
DOI: 10.1016/j.psyneuen.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Maastricht Acute Stress Test (MAST): A quick and non-invasive approach to elicit robust autonomic and glucocorticoid stress responses

Abstract: Stress-related research has employed several procedures to activate the human stress system. Two of the most commonly used laboratory paradigms are the Trier Social Stress Test (TSST) and the Cold Pressor Test (CPT). We combined their most stressful features to create a simple laboratory stress test capable of eliciting strong autonomic and glucocorticoid stress responses. In comparison with the CPT and its variations, our stress tool (labeled the Maastricht Acute Stress Test; MAST) was found to yield superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
296
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 286 publications
(316 citation statements)
references
References 51 publications
18
296
2
Order By: Relevance
“…We utilized the MAST because it combines a physical stressor (i.e., a cold pressor challenge) with a social-evaluative (i.e., mental arithmetic) component, but does not require the presence of a panel. However, despite it previously (Smeets et al, 2012) been shown to yield similar subjective and cortisol stress responses to the TSST (which includes a panel), our findings suggest that it may not always be as effective as the TSST. Future research should explore further the utility of the MAST in a range of different samples and conduct additional evaluation on whether there is a need for a stronger social-evaluative component.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…We utilized the MAST because it combines a physical stressor (i.e., a cold pressor challenge) with a social-evaluative (i.e., mental arithmetic) component, but does not require the presence of a panel. However, despite it previously (Smeets et al, 2012) been shown to yield similar subjective and cortisol stress responses to the TSST (which includes a panel), our findings suggest that it may not always be as effective as the TSST. Future research should explore further the utility of the MAST in a range of different samples and conduct additional evaluation on whether there is a need for a stronger social-evaluative component.…”
Section: Discussioncontrasting
confidence: 81%
“…The MAST is a recently developed stress protocol designed to be both physiologically and psychologically challenging by combining an uncontrollable physical stressor (i.e., a cold pressor challenge) with a social-evaluative (i.e., mental arithmetic) component (Smeets et al, 2012). In addition, it has been shown to yield similar subjective and cortisol stress responses to the Trier Social Stress Test (TSST), however, it does not require the presence of a panel (see Kirschbaum et al, 1993).…”
Section: Maastricht Acute Stress Test (Mast)mentioning
confidence: 99%
“…For example, in the socially evaluated cold pressor test (SECPT) participants are asked to perform a traditional CPT while being video-taped and watched by an experimenter 24 . Similarly, the Maastricht Acute Stress Test integrates SECPT with public speaking and mental arithmetic components of the TSST 25 . While these approaches represent a significant step forward in stress research it remains important to examine the specific, and potentially dissociable, influence of SAM and HPA activation on the neural correlates of behavior, cognition, and emotion.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, at baseline, high ruminating individuals already Overall increased levels of salivary cortisol and negative disturbances in mood after stress induction (MAST) proved its eff ectiveness in elucidating a biological and aff ective stress response, corresponding to previously reported work on the eff ects of the MAST (Smeets et al, 2012). Contrary to expectations S'/S'-allele carriers did not show a heightened cortisol stress responsiveness.…”
Section: Stress Inductionmentioning
confidence: 83%
“…This task has shown great reliability and validity in inducing both cognitive and physiological stress responses by combining elements of the classic Trier Social Stress Test and the Cold Pressor Task (Smeets et al, 2012).…”
Section: Stress Inductionmentioning
confidence: 99%